1970
DOI: 10.1039/c29700000002
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohepta-amylose inclusion complexes. A proton magnetic resonance study

Abstract: Sztmmary Proton magnetic resonance provides direct evidence for the inclusion nature of cycloheph-amylose complex formation with aromatic substrates.CYCLOAMYLOSBS (cyclodextrins) have been used as models for enzymes1P2 and proteins,3p4 because their structures are well defined3 s5 p6 and because they interact with many substrates in a manner similar to that of enzymes and proteins. It has been ~uggestedl-~ p7 y 8 that cycloamyloses form inclusion complexes with organic substrates in aqueous solution. Little di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
6

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(96 citation statements)
references
References 0 publications
4
86
0
6
Order By: Relevance
“…The upfield shifts observed for the signals of H-3' and H-5', situated inside the β-CD cavity, and concomitant downfield shift changes for enalapril maleate protons in the 1 H NMR spectra of mixtures of enalapril maleate and β-CD are a clear indication of complexation between enalapril maleate and β-CD, in analogy to previous studies 5,6 . Furthermore, the magnitude of shift changes of these β-CD protons increased with the increase in the concentration of enalapril maleate.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The upfield shifts observed for the signals of H-3' and H-5', situated inside the β-CD cavity, and concomitant downfield shift changes for enalapril maleate protons in the 1 H NMR spectra of mixtures of enalapril maleate and β-CD are a clear indication of complexation between enalapril maleate and β-CD, in analogy to previous studies 5,6 . Furthermore, the magnitude of shift changes of these β-CD protons increased with the increase in the concentration of enalapril maleate.…”
Section: Resultssupporting
confidence: 86%
“…A variety of techniques are used, for characterization of inclusion complexes in terms of geometry and configurational preferences, of which solid state and high resolution NMR spectroscopy are most important 5 . The formation of inclusion complex results in the shift changes in resonances of both the CDs and the guest protons 6 . The magnitude of Δδ is a critical function of position of proton in the molecule, size of CD cavity as well as host/guest ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the inclusion complex between -ketotosylate molecule and -CD results in chemical shift changes of cyclodextrin. The inclusion of an aromatic guest into the cyclodextrin cavity results in upfield shifts of the H-3 and H-5 of cyclodextrin, due to the ring-current effect of the aromatic ring (Demarco & Thakkar, 1970). Study of 1 H NMR (DMSO) of the -CD, -CD-phenacyl tosylate complex, and freeze-dried reaction mixtures of -CDphenacyl tosylate-thiourea indicated up field shift of H-3 and H-5 protons in the complex as well as in the reaction mass after 30 min.…”
Section: Thiazolesmentioning
confidence: 99%
“…... clusion complexes. 16) The cyclodextrin molecule is doughnut-shaped. It has been reported that if certain "guest" compounds mig-rate into the interior of the cavity of the cyclodextrin, the H-3 and H-5 protons, located within the cavity, will be strongly shielded.…”
Section: B Effect Of F3-cyclodextrin On the Solubilities Of Naringinmentioning
confidence: 99%